Seasonal variation in the detection rate and all-cause in-hospital mortality of AKI in China: A nationwide cohort study - Li, Jiaqi; Zhou, Qingqing; Zhang, Daoning; Wang, Jinwei; Yang, Li (Frontiers in Public Health, 2022)
Background: Acute kidney injury (AKI) is a severe clinical syndrome that places a massive burden on medical systems worldwide, yet the seasonality of AKI remains unexplored in China. This study aimed to describe the seasonal variation in the detection rate and all-cause in-hospital mortality of AKI in China based on a nationwide survey. Methods: This was a retrospective cohort recruiting a national sample of 7,291 adult patients treated in hospital in 22 provinces of mainland China during January or July 2013. AKI was defined according to the 2012 Kidney Disease Improving Global Outcomes AKI creatinine criteria or expanded criteria of increase or decrease in serum creatinine level of 50% during the hospital stay. The seasonal group was determined according to the corresponding admission date for each patient. The detection rate of AKI refers to the ratio of identified AKI cases to the total number of adult admissions from the same regional or seasonal group. Results: Both the detection rate (2.31% vs. 2.08%, p=0.001) and in-hospital mortality rate (13.3% vs 10.7%, p=0.001) of AKI were higher in winter than in summer. The AKI patients detected in winter had higher proportions of prehistory diseases, cardiac or vascular kidney injury factors, and severe comorbidities than those in summer (all p<0.05). In the multivariable analysis, winter was an independent risk factor for in-hospital mortality of AKI patients (odds ratio [OR]=1.22, 95% confidence interval [CI], 1.03-1.44, p=0.02) after adjusting for demographic factors, medical history, comorbidity, and climatic confounders. Higher ambient temperature (OR=0.91, 95% CI, 0.86-0.97, p=0.002, per 10 °C increase), higher relative humidity level (OR=1.14, 95% CI, 1.04-1.25, p=0.005, per 10% increase), and living in temperate continental region (OR= 2.18, 95% CI, 1.63-2.91, p<0.001) were each independently associated with in-hospital mortality. Conclusion: The detection rate and all-cause in-hospital mortality of AKI showed a winter predominance in AKI patients in China. Winter appeared to be an independent risk factor for all-cause in-hospital mortality in AKI patients. Environmental factors, including lower ambient temperature, higher relative humidity level, and living in temperate continental climatic regions, were each independently associated with increased risks of in-hospital mortality in AKI patients.